Delineation of selected Western Australian Amanita mycoflora by macroscopic, microscopic and DNA sequence analysis - McGurk, Laurton E (Curtin University, 2014)
Seven undescribed, and two described, taxa of the Amanita genus have been delineated using three techniques. The macroscopic and microscopic traits of the basidiomes of each collection distinguish them from each other and from other Amanita species. The microscopic traits reveal an affinity with the basal taxa the Amanita. Analysis of rDNA sequences show that these WA species are distinct from overseas Amanita taxa.